ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SOCRE DAN MODEL INTERNAL GROWTH RATE - Dian Safitri; Dina Fitri Septarini (Musamus Accounting Journal, 2018)
Analysis of Bankruptcy Prediction Using Altman Z-Score Model and Internal Growth Rate Model An Empirical Study on Delisting Companies from Indonesia Stock Exchange Year 2012-2015. This study aims to predict bankruptcy using the Altman Z Score model and the Internal Growth Rate model in delisting companies from the Indonesia Stock Exchange in 2012-2015 and to find the most appropriate model in predicting bankruptcy.The number of companies studied were 12 companies delisted from the Indonesia Stock Exchange 2012-2015 with a year of observation for 3 years before delisting, so that the object of research selected as many as 36 objects of research, with the object that can be studied as many as 24 research objects. The data used is secondary data. Analytical techniques used are Altman Z-Score model and Internal Growth Rate model.Results from 24 objects of the research using modification Altman Z-Score model there are 10 objects that fall into the category of bankruptcy. While using the Internal Growth Rate model there are 12 companies that fall into the category of bankruptcy. From the results of the analysis can be seen that the model of Internal Growth Rate is more appropriate and easier to use to shave bankruptcy of 12 companies delisting from the Indonesia Stock Exchange. Keywords: Altman Z-Score, Internal Growth Rate, and Prediction of bankruptcy.